Louis XIV and the peace of Europe - Condren, John, 1986- author.
1 online resource (xx, 243 pages)
Keywords: "In recent generations, the study of dynastic politics and diplomatic history has undergone a revival. This field provides invaluable context for understanding international relations, and focuses on aspects of cultural exchange and intellectual currents far more than previously. The "age of Louis XIV" has not been immune from this resurrection of interest in foreign policy and the conduct of diplomacy. This book is the first serious full-length study of Louis XIV's diplomatic relations with the small states of northern Italy, specifically the duchies of Parma, Modena, and Mantua-Monferrato. Louis's desire to be seen as a peacemaker (despite his obvious bellicosity) extended to Italy, where he asserted the French crown's potential as a broker of peace between rival dynasties. But his evident self-interest, and the need to preserve France's perceived traditional alliance with the House of Savoy, undermined these efforts. He also failed to defend the interests of the dukes of Parma and Modena in their quarrels with the Holy See. After apparent successes in the Franco-Dutch War, Louis believed that he could undermine Spanish influence over the princes of Italy. But his attempts to do so antagonised both the Austrian and Spanish Habsburgs and the Lombardy dukes themselves, resulting in renewed war. Louis XIV and the Peace of Europe analyses diplomatic culture at Versailles and at the small Italian courts, and assesses examples of artistic exchange. It will be valuable reading for undergraduates, graduate students, and historians of the field, as well as for those interested in Louis XIV and Italian culture more generally"--